The use of shadow prices in capital rationing problem - BAALOUDJ, B (Journal of Human Sciences, 2002)
The aim of this article is to examine the use of linear programming to transfer funds from earlier to later periods by using the shadow prices as indicators in the transferring process, taking into consideration that each final budget period should not be greater than the sum of the starting budgets and the amount which can be transferred from its preceding periods. This method of transferring funds has two advantages, an increase in the objective function without using external resources. In some cases, the problem of accepting fractional projects can be overcome.